2009
DOI: 10.1002/glia.20884
|View full text |Cite
|
Sign up to set email alerts
|

Elastin‐derived peptides: Matrikines critical for glioblastoma cell aggressiveness in a 3‐D system

Abstract: In the most common primary brain tumors, malignant glioma cells invade the extracellular matrix (ECM) and proliferate rapidly in the cerebral tissue, which is mainly composed of hyaluronan (HA) along with the elastin present in the basement membrane of blood vessels. To determine the role of ECM components in the invasive capacity of glioma cell lines, we developed a 3-D cell-culture system, based on a hydrogel in which HA can be coreticulated with kappa-elastin (HA-kappaE). Using this system, the invasiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 45 publications
(52 reference statements)
3
48
1
Order By: Relevance
“…EDP stimulate the proliferation of normal cells, such as fibroblasts [9,54,55] and smooth muscle cells [56], but also tumor cells from glioblastoma [57] and melanoma [15]. Consistently with literature data, our results demonstrated that EDP induce cell proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…EDP stimulate the proliferation of normal cells, such as fibroblasts [9,54,55] and smooth muscle cells [56], but also tumor cells from glioblastoma [57] and melanoma [15]. Consistently with literature data, our results demonstrated that EDP induce cell proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to its role in the development of microfibrils, another important role of MFAP-4 in the suppression of MMP-12 activity is illustrated both in our in vivo and in vitro analyses. In parallel with previous studies indicating that elastin-derived peptides induce the expression of various kinds of MMPs (including MMP-12) in several types of cells5253 and that UV radiation alone is sufficient to selectively degrade many elastic fiber associated proteins54, the enhancement of MFAP-4 is thought to be in charge of the suppression of MMP-12 activity as well as the promotion of microfibril formation which is essential for the organization of functional elastic fibers, resulting in the observed photoprotection.…”
Section: Discussionsupporting
confidence: 89%
“…As the threshold for elastin expression in the adult is unknown, it could be possible that the slight increase in elastin mRNA is sufficient for protein expression. Additionally, it has been reported that tropoelastin expression can cause a positive-feedback loop, which could increase levels beyond our initial mRNA findings (Coquerel et al, 2009; Wachi et al, 1995). There also may be feedback to associated elastic fibers proteins, which may regulate elastin as well.…”
Section: Discussioncontrasting
confidence: 50%